Peran Pemberdayaan Wakaf Tunai (Studi Kasus Pada BMT Amanah Ummah Surabaya) - Nur Liviasari Yulma; Sri Herianingrum (Universitas Airlangga, 2016)
This study aims to determine the role of Amanah Ummah BMT in cash waqf empowerment, this study also aims to determine the outcome on the empowerment of cash waqf carried out by Amanah Ummah BMT. These became the interview questions’ base to determine the role of Amanah Ummah BMT in cash waqf empowerment and the success of the cash waqf empowerment.This study uses qualitative approach with descriptive methods. Subjects in this study is the Manager of Surabaya Amanah Ummah BMT and the mauquf alaih who receive cash waqf.Based on the research results indicate that the role of the Amanah Ummah BMT as fund-collecting institution also as cash waqf Nazhir can be considered well because it can collect, manage and distribute cash waqf right on target. It can be seen from how the success indicators of the cash waqf empowerment program byAmanah Ummmah BMT are fulfilled.